2012
DOI: 10.1186/1475-2867-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network profiling of U373MG human glioblastoma cells following induction of apoptosis by novel marine-derived anti-cancer 1,2,3,4-tetrahydroisoquinoline alkaloids

Abstract: BackgroundGlioblastoma is the most aggressive form of brain tumors showing resistance to treatment with various chemotherapeutic agents. The most effective way to eradicate glioblastoma requires the concurrent inhibition of multiple signaling pathways and target molecules involved in the progression of glioblastoma. Recently, we obtained a series of 1,2,3,4-tetrahydroisoquinoline alkaloids with potent anti-cancer activities, including ecteinascidin-770 (ET-770; the compound 1a) and renieramycin M (RM; the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Complete surgical resection of the glioma is impeded by this type of tumor growth, which is the reason for tumor recurrence and the necessity for chemotherapy. There are new experimental strategies for the treatment of glioma, especially regarding the mechanisms related to programmed cell death, 3,4 that are raising hopes in cancer treatment. However, even the best drugs have strong negative effects on healthy cells and are distributed within the organism in an uncontrolled way.…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical resection of the glioma is impeded by this type of tumor growth, which is the reason for tumor recurrence and the necessity for chemotherapy. There are new experimental strategies for the treatment of glioma, especially regarding the mechanisms related to programmed cell death, 3,4 that are raising hopes in cancer treatment. However, even the best drugs have strong negative effects on healthy cells and are distributed within the organism in an uncontrolled way.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, there are new experimental strategies for the treatment of glioma, including mechanisms associated with programmed cell death, raising hopes for effective cancer treatments. 3 Our recent studies have shown that carbon nanomaterials may have potential applications in cancer therapy. 4,5 One of the carbon allotropes that can potentially be used in cancer treatment is graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, EGFR plays a vital role in various aspects of malignancy, particularly in tumor cell proliferation, survival and metastasis (4,5). Glioma-associated EGFR mutant forms show constitutive kinase activity that chronically stimulates Ras signaling to drive cell cycle progression and also activates the PI3K/AKT pathway to promote cellular proliferation and migration (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%